Message from the Editor-in-Chief - Shen, Han-Wei (IEEE transactions on visualization and computer graphics, 2025)
Welcome to the January 2025 issue of the IEEE Transactions on Visualization and Computer Graphics (TVCG). This is my second IEEE VIS special issue as Editor-in-Chief, and I am very excited to introduce it to you all. As in the previous three years, the papers submitted to IEEE VIS were categorized into six major research subareas: Theoretical & Empirical (112 papers), Applications (154), Systems & Rendering (51), Representations & Interaction (110), Data Transformations (53) and Analytics & Decisions (77). The conference took place in St. Pete Beach, Florida, USA, during October 13-18, 2024. Included in this special issue are the top 124 papers selected by the Program Committee from a total of 557 submissions.